2006
DOI: 10.1364/ao.45.008674
|View full text |Cite
|
Sign up to set email alerts
|

Optics and mechanisms for the Extreme-Ultraviolet Imaging Spectrometer on the Solar-B satellite

Abstract: The Extreme-Ultraviolet Imaging Spectrometer (EIS) is the first of a new generation of normal-incidence, two-optical-element spectroscopic instruments developed for space solar extreme-ultraviolet astronomy. The instrument is currently mounted on the Solar-B satellite for a planned launch in late 2006. The instrument observes in two spectral bands, 170-210 A and 250-290 A. The spectrograph geometry and grating prescription were optimized to obtain excellent imaging while still maintaining readily achievable ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…Thus, in the absence of other sources of line broadening and assuming a total Gaussian line shape, the total observed Fe XVI line FWHM should be approximately W = W 2 th + W 2 inst = 0.078 Å . Before its launch, the instrumental profile of EIS was laboratory tested (Korendyke et al 2006) using a limited set of line observations. Although the line profiles were not analysed rigorously, it was concluded that the instrumental profile was adequately fitted with a Gaussian profile, and this is the assumption made in this paper.…”
Section: Hinode Eis Observations Of Fe XVImentioning
confidence: 99%
“…Thus, in the absence of other sources of line broadening and assuming a total Gaussian line shape, the total observed Fe XVI line FWHM should be approximately W = W 2 th + W 2 inst = 0.078 Å . Before its launch, the instrumental profile of EIS was laboratory tested (Korendyke et al 2006) using a limited set of line observations. Although the line profiles were not analysed rigorously, it was concluded that the instrumental profile was adequately fitted with a Gaussian profile, and this is the assumption made in this paper.…”
Section: Hinode Eis Observations Of Fe XVImentioning
confidence: 99%
“…The instrument has 1Љ spatial pixels and 22.3 m spec-Å A tral pixels. Further details are given in Culhane et al (2007) and Korendyke et al (2006).…”
Section: Observationsmentioning
confidence: 99%
“…However, as the λ209.9 line is located at the long wavelength edge of the EIS wavelength band, the uncertainties in sensitivity of the EIS instrument must be considered. In our analysis, the calibration performed at Naval Research Laboratory (NRL) before the launch is adopted to obtain the spectral sensitivity of the EIS instrument (Korendyke et al 2006).…”
Section: Active Region Data Setmentioning
confidence: 99%